Forest related perspectives for regional development in Europe - Hyttinen, Pentti (Research report (European Forest Institute) ;, 2002)
Most of the less-favoured regions in Europe feature large areas of forestland. The FORWARD (Forest Resources for Work Opportunities and Regional Development) project was initiated to generate employment and income based on forest resources. This report presents the findings of the project.